Single versus Multiple Mini-tract Percutaneous Nephrolithotomy for Staghorn Renal Stone: A Single-Center Study - Khan, Jamil Ahmed (Biological and Clinical Sciences Research Journal, 2025)
Staghorn stones are difficult to treat, which may cause severe complications in the urinary tract. So surgical intervention is necessary. Objective: This study aimed to determine the outcomes of Single versus multiple mini-tract percutaneous nephrolithotomy for Staghorn Renal Stones. Methods: The present randomized controlled trial was conducted at the Department of Urology, Postgraduate Medical Institute (PGMI), Quetta, from January 2025 to June 2025, following permission from the hospital’s ethical committee. Individuals of both genders and different age groups with complete or partial staghorn stones and scattered renal stones involving both renal pelvis and calyces were included. The study participants were divided into two groups: Group A and Group B. Each group has 55 individuals. Group A received a single mini-tract (21-Fr sheath) via the percutaneous method, and Group B required multiple mini-tracts (two). To determine the location, dimensions, and hardness of the stones, as well as the anatomy of the renal collecting system, for continuous variables (such as patient characteristics and perioperative data), an independent-sample t-test was employed. The perioperative findings and postoperative outcomes were compared. Statistical analysis was performed using SPSS. Results: A total of 110 individuals with satghorn stones were enrolled in this study, which were randomly divided into single (A) and multiple (B) tract PCNL groups. In a single tract, the mean stone size was 11.68 ± 8.07, whereas in multiple tracts, it was 16.24 ± 10.50. Consequently, there was a notable variation in stone size between the two groups (P = 0.005). When comparing the two groups’ operative times, the mean time for a single tract was 101±11.0 minutes, while the mean time for multiple tracts was 121±23.6 minutes (p-value of 0.005). A single-tract hospital stay lasted 4.20±2.21 days, while a multiple-tract hospital stay lasted 4.21±2.10 days. Likewise, 28% of blood transfusions occurred in a single tract, while 16% occurred in multiple tracts. Clavien-Dindo was assigned to the complication of blood transfusion and bleeding, which were the most serious adverse effects associated with the multiple-tract strategy compared to single-tract therapies. Conclusion: The present study concluded that a safe and effective technique for treating staghorn kidney stones is multiple-tract access during PCNL.